Epithelial-to-mesenchymal transition is an active process in the large airways of patients with asthma-COPD overlap and partially abrogated by inhaled corticosteroid treatment: a bronchoscopy endobronchial biopsy study - Surajit Dey; Wenying Lu; Prabuddha S. Pathinayake; Maddison Waters; Greg Haug; Josie Larby; Heinrich C. Weber; Peter A. B. Wark; Peter A. B. Wark; Mathew Suji Eapen; Sukhwinder Singh Sohal (Frontiers in Immunology)
IntroductionAsthma and chronic obstructive pulmonary disease (COPD) overlap (ACO) is a term used to describe a patient with coexisting clinical features of asthma and COPD. We have previously reported that epithelial to mesenchymal transition (EMT) is active in the lungs of patients with COPD however, EMT in ACO remains an unexplored area. We hypothesize that EMT is an active process in ACO.MethodsIn this cross-sectional study, large airway endobronchial biopsy (EBB) tissues from patients with asthma (14), COPD (22), current (CS) and ex-smokers (ES), and ACO (12) were immunohistochemically stained for EMT markers (E and N cadherin, vimentin, S100A4, and Collagen IV) and compared with 12 current smokers with normal lung function (NLFS) and 10 non-smoking healthy control (HC) subjects. In addition, air-liquid interface (ALI) cell cultures were performed and cells from patients with ACO and HC were treated with TGF-β, IL-13 and cigarette smoke extract (CSE). Later cells from ALI cultures were lysed for Immunoblotting. Immunostained tissues were enumerated for percent expression of E and N-Cadherin in the epithelium, vimentin and S100A4 positive cells both in the epithelium and reticular basement membrane (RBM). Additionally, the degree of RBM fragmentation was evaluated, a key tissue structural marker of EMT.ResultsCompared to healthy controls and asthmatics, ACO had the greatest fragmentation of RBM (P < 0.01). ACO also had substantially decreased percentage expression of E-cadherin (P <0.01), increase percentage of N-cadherin expression, and higher vimentin and S100A4 positive basal cells, in comparison to healthy controls. In the RBM of ACO, S100A4 positive cells (P <0.05) and Vimentin-positive cells were markedly higher in comparison to HC. Similar changes were observed with western blots in response to Th-2 cytokine IL-13, CSE and EMT activator TGF-β.ConclusionsThese data are suggestive of active EMT in ACO. Additionally, 50% of the patients with ACO were on 800 mcg/day inhaled corticosteroid (ICS) treatment which may have abrogated some EMT activity; however, it suggests protective effects of ICS as we previously reported in COPD. Studies with larger cohorts are needed to further confirm ICS effects in ACO.